Nature of Nitrogen Mineralization and Carbon Dioxide Evolution in some Typical Bihar Soils - Sinha, P; Jha, K.K.; Singh, R. (Journal of Soil and Water Conservation, 2022)
organic matter plays a key role in soil fertility and soil conservation. It improves soil fertility by improving physical condition of the soil and making plant nutrients available. Many of the agronomic measures suggested for soil con- servation aim at maintenance of a good supply of organic matter in the soil. The question of maintenance of organic matter in a soil is closely linked with its decomposi- tion. Decomposition of organic matter results in humus formation and release of plant nutrients. It is, therefore, essential that for proper conservation of soil, a continued supply of organic matter should be so adjusted as to cope with its decomposition in the soil. Thus soil fertility and soil conser- vation are closely linked with each other. It is, therefore, very important to study the nature and extent of organic matter decomposition in soil. The end products of the decomposition of organic matter are humus, C02, water and simple salts of N, P, Ca, K, etc. Apart from humus formation, C02 evolution and ammonia production are main processes involved in the decomposition of the organic matter. Workers in the field have, therefore, studied the decomposition of organic matter mainly from these two angles, i.e. C02 evolution and N minera- lization which have often been correlated with soil fertility. Very scanty information at present is available on the decomposition of organic matter in Bihar soils and the present investigation was, therefore, con- ducted to study the nature and decomposi- tion of organic matter present in Bihar soils with respect to both C02 evolution and N mineralization aspects. To start with 10 typical soils from all over the State of Bihar were selected for studies. Soil samples from these arcas included only upland tracts in the present investigations. Studies on low. land soils of these areas will be taken up later on.